Estudo da perda dental e do sono em pacientes após acidente vascular cerebral - Vago, Eliana Regina Lottenberg [UNIFESP] (2019)
Objective: To evaluate sleep quality, excessive daytime sleepiness, risk for obstructive sleep apnea (OSA) and the frequency of edentulism, as well as the use or not of prostheses in patients following stroke. Methods: This is a transversal and observational investigation. 130 patients’ post- stroke participated in this study. The data collected were age, sex, BMI, TOAST, NIHSS, stroke type, modified Rankin Scale, comorbidity presence such as hypertension, diabetes mellitus and smoking. We measured through the application of questionnaires quality of life (SF-36), sleep quality (PSQI), risk for OSA (STOP- BANG) and excessive daytime somnolence (ESE). Results: Of the 130 patients included, 52.32% were male. Mean age of 59.7 ± 12.53 2 years. The average BMI was 26.36 ± 5.00 kg/m . The prevalence of ischemic stroke was 94.62%. According to Rankin's scale (1.66, ± 1.15) patients were considered with minimal sequelae and were classified as independent. For sleep quality, our sample demonstrated bad sleep quality at PSQI (7.13 ± 3.84). Our participants were at high risk for OSA according to the results from STOP BANG (4.11 ± 1.57) and did not present excessive daytime somnolence as seen by the Epworth Sleepiness Scale (8.16 ± 5.22). In relation to the teeth, the patients had 9 to 31 teeth (48,86%) or were edentate (26.15%), 60.77% used total and removable prostheses and half of them slept with them. At oral cavity evaluation, patients presented Mallampati classification III and IV (14,62% e 71,54%, respectively), elongated soft palate (72,32%), both predictors of OSA. Conclusion: Patients following stroke presented poor sleep quality, high risk for OSA, high frequency of missing teeth, anatomical variations predisposing to OSA, and it was not observed that the use of prostheses during sleep has benefited patients.